How School Environment and Self-Efficacy Affect Learning Burnout and Motivation in Accounting Students - Nursakdiah; Syuhada, Siti; Mayasari; Rifki, Ahmad; Sitompul, Kristober (Eduscape : Journal of Education Insight, 2025)
This study aims to analyze the direct and indirect effects of several factors on students' learning burnout and motivation, including (1) the school environment on learning burnout, (2) self-efficacy on learning burnout, (3) the school environment on learning motivation, (4) self-efficacy on learning motivation, (5) learning burnout on learning motivation, (6) the school environment on learning motivation through learning burnout, and (7) self-efficacy on learning motivation through learning burnout. This research is categorized as explanatory research, which seeks to explain each variable through hypothesis testing. Researchers use path analysis using SPSS 22.0 for Windows. The population of this study consists of 108 eleventh-grade students from a public vocational school (SMK Negeri) in Sarolangun Regency, with the entire population serving as the sample, applying a saturated sampling technique. The results of the study conclude that (1) Students' learning burnout is directly impacted negatively by the school environment; 2) Students' learning burnout is directly impacted negatively by self-efficacy; (3) Students' learning motivation is directly impacted positively by the school environment; (4) students’ learning motivation is directly impacted positively by self-efficacy; (5) students’ learning motivation is directly impacted positively by learning burnout (6) The school environment influences students' learning motivation through learning burnout, and (7) Self-efficacy influences students' learning motivation through learning burnout.